Unforgivable: an abusive priest and the church that sent him abroad - O'Neill, Kevin Lewis (University of California Press, 2025)
"Clerical sexual abuse is as global as the Roman Catholic Church, with bishops moving credibly accused priests not simply between parishes but also across international borders. Unforgivable follows the movement of one such perpetrator from the Great Plains of central Minnesota to the Indigenous highlands of Guatemala, where this priest had access to children and even raised one as his own. While Father David Roney provides the backbone of the story in Unforgivable, author Kevin Lewis O'Neill offers ample evidence that offshoring priests is a common practice. These maneuvers and the callous indifference of the Church once caught red-handed reveal the limits of justice. They also lay bare the disturbing fact that the scale of clerical sexual abuse is far bigger than anyone has yet considered. Rigorously researched and viscerally important, this book raises urgent questions about holding the Catholic Church accountable"--